REACH Story of Change: Protecting groundwater for climate resilience and water security in Turkana - REACH (University of Oxford, 2023)
In Turkana County, lack of research and data around Lodwar’s underlying aquifers, the Lodwar Alluvial Aquifer System (LAAS), has been a critical limitation to the sustainable development and management of groundwater resources. Research by the University of Nairobi is addressing these data and knowledge gaps, with groundwater quality mapping indicating areas with poor groundwater quality to inform water infrastructure investments. This work is contributing to new policy and practice to protect the Lodwar Alluvial Aquifer System and enhance resilience to climate risks.